2020
DOI: 10.12982/cmujns.2020.0015
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Strongyle Infection in Thoroughbred Horses of Punjab Province, Pakistan

Abstract: Strongyle infection among horses is complex and produces an inflammatory enteropathy resulting in impaired intestinal motility and microcirculation. In this study, presence of strongylosis was determined by fecal examination for nematode eggs in thoroughbred horses of Punjab Province, Pakistan. A cross sectional study was conducted from January to December 2017 in four districts of Punjab province namely Sahiwal, Lahore, Sargodha and Mandi Baha-ud-Din. A total of 2,400 fecal samples were collected from horses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…In contrast to our findings, [19,30] found statistically insignificant differences between age groups at p ≤ 0:05. The current study's findings support previous researchers' findings, which can be explained by the fact that younger animals may be more susceptible to Strongyle infestation than older animals.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, [19,30] found statistically insignificant differences between age groups at p ≤ 0:05. The current study's findings support previous researchers' findings, which can be explained by the fact that younger animals may be more susceptible to Strongyle infestation than older animals.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, the infestation rate of Strongyle revealed that younger horses appeared to be more susceptible to the disease under study. The findings are consistent with those of [27][28][29] Researchers, on the other hand, investigated and reported that adult and older horses harbored more Strongylosis than young horses, as recognized by [15], in adults, while [30] recognize that in older horses. Both arguments run counter to the current outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the research participants' experiences, getting a diagnosis was difficult because, for many years, the mode of transmission of polio was not even widely understood. The symptoms were similar to those of an ordinary flu (Altenbaugh, 2006; Highley, 2016; Khan, 2010; Oshinsky, 2005; Trevelyan et al., 2005), and the doctors and nurses did not know what to do with the symptoms (Highley, 2016). In Finland, the polio epidemic occurred from the 1940s to the 1960s, which cast a shadow during World War II and, in turn, delayed the development of medical skills and the time for rebuilding Finland.…”
Section: Discussionmentioning
confidence: 98%
“…Polio has no medical cure, but it can be treated. Vaccination is the most effective means of prevention (Altenbaugh, 2015; Khan, 2010; Oshinsky, 2005; Trevelyan et al., 2005). Polio still occurs in some regions of Asia and Africa (World Health Organization, 2021).…”
Section: Introductionmentioning
confidence: 99%